Effects of single green tea ingestion on pharmacokinetics of nadolol in healthy volunteers. Issue 11 (12th May 2020) - Misaka, Shingen; Abe, Osamu; Ono, Tomoyuki; Ono, Yuko; Ogata, Hiroshi; Miura, Itaru; Shikama, Yayoi; Fromm, Martin F.; Yabe, Hirooki; Shimomura, Kenju
Abstract : Aims: The aim of this study was to investigate the effects of a single green tea (GT), administered concomitantly or 1 hour before nadolol intake on nadolol pharmacokinetics. Methods: In a randomized 3‐phase crossover study, 11 healthy volunteers received an oral administration of nadolol with, or 1 hour after preingestion of brewed GT, or with water in a volume of 150 mL. Results: Geometric mean ratio with 90% confidence interval for nadolol AUC0–48 was 0.371 (0.303–0.439) with concomitant GT. In addition, ingestion of GT 1 hour before nadolol administration resulted in a significant reduction of nadolol AUC0–48 with geometric mean ratio of 0.536 (0.406–0.665). There were no differences in time to maximal plasma concentration and renal clearance of nadolol among groups. Conclusion: These results suggest that single concomitant ingestion of GT substantially decreases plasma concentrations of nadolol. Moreover, the reduction in nadolol bioavailability could persist for at least 1 hour after drinking a cup of GT.